Adiposity Estimated Using Dual Energy X‐Ray Absorptiometry and Body Mass Index and Its Association with Cognition in Elderly Adults. Issue 12 (December 2014) - Smith, Evelyn; Bailey, Phoebe E.; Crawford, John; Samaras, Katherine; Baune, Bernhard T.; Campbell, Lesley; Kochan, Nicole; Menant, Jasmine; Sturnieks, Daina L.; Brodaty, Henry; Sachdev, Perminder; Trollor, Julian N.
<x xml:space="preserve">Abstract</x> Objectives To determine whether obesity, estimated according to body mass index (BMI), waist circumference, and body fat and abdominal fat assessed using dual‐energy X‐ray absorptiometry (DEXA), was associated with cognitive performance. Design Cross‐sectional. Setting Community based. Participants Individuals aged 74–94 (N = 406). Measurements BMI, waist circumference, body fat, and abdominal fat were assessed using DEXA. Cognitive performance was assessed using a comprehensive neuropsychological battery. Results When categorized using BMI, overweight individuals had higher global cognitive function and executive function scores than normal‐weight individuals. This relationship did not differ according to sex. When categorized according to DEXA, there were no relationships between body fat and cognitive function in the whole group, but women in the middle and highest tertiles of DEXA body fat had better executive function than those in the lowest tertile. Men in the middle tertile of DEXA body fat had significantly better executive function and memory than those in the lowest tertile. BMI had greater power to predict executive function than DEXA body fat. No significant associations were found between cognition and estimates of abdominal adiposity. Conclusion This study found an association between being overweight and better executive function in elderly adults; this association was stronger for the simpler BMI than the more‐elaborate DEXA measures.